Retroperitoneal liposarcoma in older person – a rare case report. (4th December 2020) - Nadukkandiyil, Navas; Valappil, Sameer; Ramadan, Marwan; Al Sulaiti, Essa; Alhamad, Hanadi Khamis
Abstract: Retroperitoneal sarcoma is relatively uncommon, constituting only 10–15 percent of all soft tissue sarcomas. The most common histologic types of RPS are liposarcoma and leiomyosarcoma. Retroperitoneal sarcoma is classified based on the amount of lipid inside the cells, the mucoid lipid and the degree of cell differentiation. It is classified into the well-differentiated, myxoid, round cell, pleomorphic and dedifferentiated types and the commonest is the pleomorphic type. Dedifferentiated liposarcomas are defined by the presence of sharply demarcated regions of non-lipogenic sarcomatous tissue within a well-differentiated tumor. This type has a vague prognosis compared to other types of sarcoma and making the histological diagnosis can be difficult. Dedifferentiated liposarcoma commonly develops in the retroperitoneum, limbs, testis, and spermatic cord. Retro peritoneal sarcoma typically produces few symptoms until they are large enough to compress or invade surrounding structures. Most tumors are already large and locally advanced at the time they are first detected. Here, we reported a case that came to medical attention as an incidentally discovered large abdominal mass in an asymptomatic or minimally symptomatic, later the mass was successfully removed and free from symptoms.